Training healthcare professionals to address gender-based violence: a virtual reality–based educational intervention - Valverde, Belén; Benet, Marta; Carrió, Mar (Frontiers in Virtual Reality, 2026)
Gender-Based Violence (GBV) remains a global concern, often under-identified due to limited healthcare professional training. This study aimed to explore the potential effect of a virtual reality (VR)-based experiential training on primary care professionals from Barcelona (n = 38). A mixed-methods design was used, including a single-group pre-post quantitative test and qualitative observations recorded during the sessions. The training comprised VR scenarios presented as 360° videos, followed by debriefing with key theoretical points. Results indicated that the VR-based training was associated with an increase in participants’ self-perception of competence, knowledge, and perspectives in addressing GBV. These findings suggest that immersive VR environments may be a useful tool for professional development and could support improved identification and management of GBV in clinical practice.